ANALYSIS OF TOURIST SATISFACTION ON PAMUTUSAN ISLAND CITY OF PADANG - Zengga Zengga; Rafidola Mareta Riesa; Rifdatul Husna; Alfatah Haries (SEAN Institute, 2023)
The purpose of this research is to describe tourist satisfaction on Pamutusan Island. The title of this research is Analysis of Tourist Satisfaction on Pamutusan Island, Padang City. this research will be conducted using the google form platform as a distribution medium that will be developed as a data collection instrument. This research goes into Descriptive research with Quantitative data. In this study the population was tourists who had visited Pamutusan Island Padang, with a sample of 100 people with non-probability sampling techniques with sampling based on age criteria over 18 years. The data used in this study are primary data and secondary data